Numerical Study on the Effectiveness of Grouting Reinforcement on the Large Heaving Floor of the Deep Retained Goaf-Side Gateroad: A Case Study in China - Zhiyi Zhang; Hideki Shimada (Energies, 2018)
To study the effectiveness of grouting reinforcement on a large heaving floor of the retained goaf-side gateroad (RGSG) at a 900 m depth in the Zhuji coal mine, a numerical model involving strain softening constitutive material was built. First, the simulated deformations of the RGSG were compared with field data to verify the reliability of the numerical model. Then, the dynamic distribution of the stress in the RGSG floor was examined to reveal the mechanism of floor heave. Finally, grouting reinforcement was proposed to control the RGSG floor, and the corresponding effectiveness was verified by improving the rock mechanics of the floor strata based on the results of numerical uniaxial compressive tests. The results demonstrated that a fairly good match was achieved between the field and numerical data, and the proposed FLAC3D (Fast Lagrangian Analysis of Continua) numerical model was an effective approach to study the stability of the deep RGSG. A variation of the ratio between horizontal stress to vertical stress in the floor strata was the root cause of floor heave in the deep RGSG. Ideally, the floor heave could be reduced by 41%, 62%, and 79% when the floor strata of 1 m depth were reinforced with grouting schemes I, II, and III, respectively.